2019
DOI: 10.1128/mbio.00303-19
|View full text |Cite
|
Sign up to set email alerts
|

Iron Corrosion via Direct Metal-Microbe Electron Transfer

Abstract: The concept that anaerobic microorganisms can directly accept electrons from Fe(0) has been controversial because direct metal-microbe electron transfer has previously only been indirectly inferred. Fe(0) oxidation was studied with Geobacter sulfurreducens strain ACL, an autotrophic strain that was previously shown to grow with electrons derived from a graphite cathode as the sole electron donor. Strain ACL grew with Fe(0) as the sole electron donor and fumarate as the electron acceptor. However, it appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 56 publications
4
117
0
Order By: Relevance
“…This conclusion was confirmed by metallic iron corrosion experiments, which can help in the understandings of microbial EEU mechanisms: if a direct electron uptake pathway is present, microbes are able to use Fe 0 as sole electron donor. Very recently, Tang et al (2019) has demonstrated direct metal electron uptake via c-OMCs in the autotrophic strain Geobacter sulfurreducens ACL. Evidences of similar EEU mechanism have been reported for two iron-corroding SRB, Desulfopila corrodens strain IS4 (Beese-Vasbender et al, 2015) and Desulfovibrio ferrophilus IS5 .…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was confirmed by metallic iron corrosion experiments, which can help in the understandings of microbial EEU mechanisms: if a direct electron uptake pathway is present, microbes are able to use Fe 0 as sole electron donor. Very recently, Tang et al (2019) has demonstrated direct metal electron uptake via c-OMCs in the autotrophic strain Geobacter sulfurreducens ACL. Evidences of similar EEU mechanism have been reported for two iron-corroding SRB, Desulfopila corrodens strain IS4 (Beese-Vasbender et al, 2015) and Desulfovibrio ferrophilus IS5 .…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that krumholzibacteria_1 had both iron oxidation and reduction genes. The capacity for iron oxidation and reduction in the same organism has been previously described in Geobacter sulfurreducens (68,69). Further studies are necessary to elucidate these potential roles of krumholzibacteria_1 in iron cycling.…”
Section: Enrichment Of a Novel Verrucomicrobia Bacteroidetes And Krmentioning
confidence: 59%
“…G. uraniireducens, which has an OmcS homolog but lacks e-pili, has phenotypes inconsistent with filament-based long-range electron transport (Butler et al, 2010;Rotaru et al, 2015;Tan et al, 2016b). OmcS is important for some forms of G. sulfurreducens extracellular electron exchange (Mehta et al, 2005;Summers et al, 2010b;Tang et al, 2019). An important question is whether OmcS exists as filaments extending from the cells in vivo or whether OmcS attached to cells or e-pili is the functionally important localization of OmcS.…”
Section: Enhancing the Expression Of Protein Nanowires Is A Strategy mentioning
confidence: 99%
“…However, in these instances OmcS localized along the surface of the cell may facilitate electron transport to e-pili (Mehta et al, 2005;Lovley, 2006) or OmcS localized along e-pili may promote electron transport between e-pili and Fe(III) oxides (Lovley, 2011). Deletion of the OmcS gene inhibited electron uptake from zero valent iron, but the cells were in close association with the metal surface, and thus would not require long filaments of OmcS extending from the cell in order to establish electrical contact via OmcS (Tang et al, 2019). An OmcS-deficient mutant did not effectively grow as the electron-accepting partner in co-cultures with G. metallireducens as the electron-donating microorganism (Summers et al, 2010a), but the requirement that G. metallireducens express e-pili for co-culture growth (Ueki et al, 2018) suggests that 712 conduits other than OmcS are important for the long-range electron transport between the 713 two species.…”
Section: Observed Phenotypes Do Not Require Omcs Filaments Emanating mentioning
confidence: 99%